Unidentified sources and rough labors: the journalistic work as space for the deployment of instability and precarity - Lagos Peralta, Alejandro Gabriel; Stange Marcus, Hans; Salinas Muñoz, Claudio (Re-presentaciones: Periodismo, comunicación y sociedad, 2019)
The present work problematizes -from a comparison between the results of the studies of Moulian and Munizaga (2003) with those of Salinas, Stange, et al (2015, 2016, 2018a and 2018b)-, the role and function of the sources not identified in the journalistic production of the Chilean press.This essay describes the main variables that constitute the journalistic source, points out the usual dangers involved in the use of unidentified sources and affirms, based on comparative studies, that these types of sources are, unfortunately, not an anomaly of the press system, but a regular and even structural resource of the news production process, with the obvious detriment that this entails.
Keywords: News sources; Unidentified sources; Press; Chile; El Mercurio; La Tercera